solve:-

Asked by Abhishek Kumar Singh | 16th Oct, 2013, 12:16: PM

Expert Answer:

abx2-(a+b)2(x-1)=0

abx2-(a+b)2x+(a+b)2=0

Using quadratic formula,

B2-4AC=(a+b)4-4ab(a+b)2

=(a+b)2[(a+b)2-4ab]

=(a+b)2(a2+b2+2ab-4ab)

=(a+b)2(a-b)2

So, sqrt (B2-4AC)=(a+b)(a-b) =(a2-b2)

x=[(a+b)2 (a2-b2)]/2ab

x=[a2+b2+2ab(a2-b2)]/2ab

x=(a+b)/b  or  x=(a+b)/a

Answered by  | 16th Oct, 2013, 12:29: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.